To Construct an Engineered (S)-Equol Resistant E. coli for in Vitro (S)-Equol Production - Li, Hailiang; Mao, Shaoming; Chen, Huahai; Zhu, Liying; Liu, Wei; Wang, Xin; Yin, Yeshi (Frontiers in Microbiology, 2018)
(S)-equol is one of the major metabolites of daidzein that is produced by human and animal gut bacteria. Most of the physiological functions of soybean isoflavones, such as anti-oxidative activity, anti-cancer activity, and cardiovascular protection have been ascribed to (S)-equol. However, only 30-50% people contain this kind of equol-producing bacteria, and therefore are able to convert daidzein to (S)-equol. Administration of (S)-equol may be more beneficial than soybean isoflavones. The aim of this study was to construct an engineered (S)-equol resistant E. coli to enhance (S)-equol production in vitro. First, transposon mutagenesis libraries were constructed and screened to isolate the (S)-equol resistant mutant E. coli strain BL21 (ydiS) in order to overcome the inhibitory effects of (S)-equol on bacterial growth. Bacterial full genome scan sequencing and in vitro overexpression results revealed that the ydiS gene was responsible for this resistance. Second, the (S)-equol-producing genes L-dznr, L-ddrc, L-dhdr, and L-thdr of Lactococcus strain 20-92 were synthesized and cloned into compatible vectors, pETDuet-1 and pCDFDuet-1. These plasmids were subsequently transformed into BL21 (DE3) and its mutant BL21 (ydiS). Both engineered BL21 (DE3) and BL21 (ydiS) could use daidzein as substrate to produce (S)-equol under both anaerobic and aerobic conditions. As expected, engineered BL21 (ydiS) had faster growth rates than BL21 (DE3) when supplemented with high concentrations of (S)-equol. The yield and the daidzein utilization ratio were higher for engineered BL21 (ydiS). Interestingly, engineered BL21 (ydiS) was able to convert daidzein to (S)-equol efficiently under aerobic conditions, providing a convenient method for (S)-equol production in vitro. In addition, a two-step method was developed to produce (S)-equol using daidzin as substrate.